2019
DOI: 10.1155/2019/3917841
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phenotypic Characteristics ofEscherichia coliIsolates from Farmed Minks in Zhucheng, China

Abstract: In this study, the prevalence, phenotypes, and clonal relationships of Escherichia coli (E. coli) strains isolated from minks were investigated. In July 2017, a total of 62 fresh faecal swab samples were randomly collected from one large-scale mink farm in Zhucheng, Shandong Province, China. In all the samples, 50 E. coli strains were isolated and then assigned to serotyping, antimicrobial susceptibility test, detection of antimicrobial resistance genes and the Class 1 integrons, and multilocus sequence typing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Another study reported from Iran had showed 77.7% resistance to ciprofloxacin, 33.3% resistance to gentamicin but no resistance to Imipenem [39]. A study from China reported higher rate of resistance to tetracycline (90%), cefixime (71.4%), and ceftazidime (66.1%) in E. coli isolates [33]. Another study from Pakistan reported higher resistance to gentamicin (77%) and ciprofloxacin (65%) in clinical isolates of Enterobacteriaceae [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study reported from Iran had showed 77.7% resistance to ciprofloxacin, 33.3% resistance to gentamicin but no resistance to Imipenem [39]. A study from China reported higher rate of resistance to tetracycline (90%), cefixime (71.4%), and ceftazidime (66.1%) in E. coli isolates [33]. Another study from Pakistan reported higher resistance to gentamicin (77%) and ciprofloxacin (65%) in clinical isolates of Enterobacteriaceae [40].…”
Section: Discussionmentioning
confidence: 98%
“…However, similar study from Bangladesh reported 100% MDR in E. coli isolates [43]. Open access between poultry farms and communities, unhygienic practice, inappropriate use of antibiotics, are some of the reasons attributed for emerging resistance patterns including MDRs in Nepal [33,43,44].…”
Section: Discussionmentioning
confidence: 98%
“…Pulsotypes A, E, I, and K (the epidemic strains) were distributed and disseminated among poultry in the Tai'an area. Multilocus sequence typing provides a scalable typing system that reflects the population and evolutionary biology of E. coli , thereby enabling valid comparisons of the results from different laboratories ( Qiu et al., 2019 ). Multilocus sequence typing of these 27 poultry-origin POL-resistant E. coli strains also showed diversity among the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Many E. coli strains in the intestinal tract of humans and animals are considered as commensal members of the microbiota [ 1 ]. However, some strains, including enteropathogenic E. coli , enteroinvasive E. coli , enteroaggregative E. coli , enterotoxigenic E. coli , and enterohemorrhagic E. coli , are highly pathogenic, and may initiate a wide spectrum of diseases ranging from self-limiting to life-threatening intestinal and extra-intestinal illnesses, such as enteritis, pyelonephritis, enterotoxaemia, mastitis, cystitis, meningitis, septicemia, and arthritis [ 1 , 2 , 3 ]. Antibiotics have long been considered the first line of defense to prevent pathogenic E. coli -associated infections.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics have long been considered the first line of defense to prevent pathogenic E. coli -associated infections. However, the treatment of pathogenic E. coli has become complicated by the rapid emergence and dissemination of antibiotic-resistant strains [ 2 ].…”
Section: Introductionmentioning
confidence: 99%